Difficulty leading interpersonal coordination: towards an embodied signature of social anxiety disorder - Varlet, Manuel; Marin, Ludovic; Capdevielle, Delphine; Del-Monte, Jonathan; Schmidt, Richard; Salesse, Robin; Boulenger, Jean-Philippe; Bardy, Benoît G.; Raffard, Stéphane (Frontiers in Behavioral Neuroscience, 2014)
Defined by a persistent fear of embarrassment or negative evaluation while engaged in social interaction or public performance, social anxiety disorder (SAD) is one of the most common psychiatric syndromes. Previous research has made a considerable effort to better understand and assess this mental disorder. However, little attention has been paid to social motor behavior of patients with SAD despite its crucial importance in daily social interactions. Previous research has shown that the coordination of arm, head or postural movements of interacting people can reflect their mental states or feelings such as social connectedness and social motives, suggesting that interpersonal movement coordination may be impaired in patients suffering from SAD. The current study was specifically aimed at determining whether SAD affects the dynamics of social motor coordination. We compared the unintentional and intentional rhythmic coordination of a SAD group (19 patients paired with control participants) with the rhythmic coordination of a control group (19 control pairs) in an interpersonal pendulum coordination task. The results demonstrated that unintentional social motor coordination was preserved with SAD while intentional coordination was impaired. More specifically, intentional coordination became impaired when patients with SAD had to lead the coordination as indicated by poorer (i.e., more variable) coordination. These differences between intentional and unintentional coordination as well as between follower and leader roles reveal an impaired coordination dynamics that is specific to SAD, and thus, opens promising research directions to better understand, assess and treat this mental disorder.